Peningkatan Kemandirian Ekonomi Keluarga dalam Memanfaatkan Limbah Serbuk Gergaji - Mutaqin, Hiban; Amin, Dang Eif Saiful; Aziz, Rohmanur (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
Pakuhaji Village there is a lot of sawdust waste that can be used for oyster mushroom cultivation. The community sees this oyster mushroom cultivation as a potential to increase their family's economic independence. The purpose of this study was to determine how community development in utilizing sawdust in Pakuhaji Village, Subang Regency, Potential utilization of sawdust, and oyster mushroom cultivation, and how the family's independence in Pakuhaji Village after using sawdust waste. The research method used is descriptive qualitative with data collection methods using observation and interviews. The analysis used uses data triangulation by confirming the data in the field and the theory used after that. a conclusion is maded that the results of this study found that increasing the family's economic independence in utilizing sawdust waste was successful.